Knowledge and Practices on Periodontal Health among Adults, Misungwi, Tanzania - Nyorobi, John Michael (Int J Dent, 2018)
The level of knowledge and practices on periodontal health of 388 adults in Misungwi District, Tanzania, was assessed. Analysis included frequency distributions and the chi-square test at a p value of 0.05. Many more participants were males (n=197; 50.8%) and of younger age group (n=215; 55.4%) and having seven years of education (n=257; 66.2%). Higher number of participants reported owning a mobile phone (n=289; 74.5%) and a radio (n=298; 76.8%), while few (n=45; 11.6%) had their houses connected to electricity. Study participants who were males (n=101; 51.3%), had more than seven years of schooling (n=67; 72.3%), who owned a mobile phone (n=143; 49%), owned a radio (n=144; 48.3%), and resided in houses having electricity (n=37; 82.2%) were statistically significantly more knowledgeable on periodontal health when compared to their counterparts. A statistical significant difference was seen in oral health practices conducive to periodontal health among those who were males (n=133; 67.0%), having more than seven years of education (n=78; 83.0%), owning a mobile phone (n=189; 65.4%), owning a radio (n=195; 65.4%), and residing in house having electricity (n=35; 77.8%). This study observed that participants who were males, owned a mobile phone, owned a radio, resided in houses having electricity, and having more than seven years of education were more knowledgeable and had more conducive oral health practices on periodontal health.